What Determines Coverage by Collective Agreements or Awards? (The Australian Journal of Labour Economics, 2019)
Wage setting in Australia features a complex system of interdependencies between awards, collective agreements (CAs) and individual arrangements (IAs). How an employee comes to have their pay and conditions set has long been the subject of close study. In the context of recent declines in collective agreement coverage, the purpose of this article is to examine the influence of the employee and employer characteristics on collective agreement coverage. The causes of that decline are not the topic of this paper, but the determinants of collective agreement coverage are, because of the substantial effects it has.JEL: J50, J52, J58